CeO2-Pr2O3 rare earth oxide nano materials for application as bioproduct in Angelica sinensis cultivation - Nguyễn, Thị Thu Phương; Cao, Văn Hoàng; Nguyễn Viết, Trung; Huỳnh, Xuân Trường; Phạm, Trần Thanh Ngân; Đặng, Thị Diệu Linh; Nguyễn, Thuý Hằng (Hue University Journal of Science: Natural Science, 2025)
In this study, CeO₂-Pr₂O₃ nano fertilizer was manufactured and utilised as a plant growth stimulant for Angelica sinensis. CeO₂-Pr₂O₃ was synthesised from cerium(IV) nitrate and praseodymium(III) nitrate as precursors via the ultrasonic-assisted co-precipitation method. The morphology and structure of the nanomaterials were characterised by using XRD, IR, EDX, SEM, and TEM. The composite CeO₂-Pr₂O₃ substantially affected the growth and development of Angelica sinensis. After 90 days of application, the plants treated with CeO₂-Pr₂O₃ nanomaterials exhibited significantly enhanced growth performance: plant height reached 37.8 cm (an increase of 36.0%); leaf number reached 37.9 leaves/plant (an increase of 37.3%), and canopy diameter reached 49.5 cm (an increase of 31.6%) compared with the control. Additionally, Angelica sinensis plants supplemented with CeO₂-Pr₂O₃ demonstrated improved morphological characteristics, including stronger stems, thicker and greener leaves, deeper purple stem colouration, and more vigorous root systems with a greater number of lateral and main roots. These findings suggest that CeO₂-Pr₂O₃ nanomaterials possess a notable plant growth-promoting effect on Angelica sinensis.